CONTRASTING LATERITIC NICKEL ORE CHARACTERISTICS IN EASTERN INDONESIA: THE URGENCY OF SHIFTING FROM RKEF TO HPAL - Renny Cahyaningtyas; Nurkhamim; Eddy Winarno (Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2026)
While Indonesia holds a strategic position in the global electric vehicle (EV) supply chain, with 19.16 billion tons of nickel resources, this dominance is threatened by a critical mismatch between geological realities and the downstream industrial structure. This paper analyzes the disparity within the national ore balance and assesses the urgency of transitioning processing technologies to secure long-term sustainability. Using an economic geology approach, we conducted a geometallurgical characterization of regional deposits (Sulawesi, Maluku, Papua) and a mass balance analysis based on the 2025 Mineral Resource and Reserve Balance. Findings indicate that 58% of national resources are limonite (Ni <1.5%) and are predominantly located in Eastern Indonesia (Maluku and Papua). Crucially, these eastern limonite profiles are enriched in cobalt, scandium, and a comprehensive spectrum of rare earth elements (REE). In stark contrast, the industry remains heavily skewed toward pyrometallurgy (RKEF) for producing intermediate stainless steel products, resulting in massive consumption of saprolite ore (Ni ≥ 1.5%). Reserve life projections indicate that high-grade saprolite could be depleted within eight years at current extraction rates. Consequently, this study advocates for a moratorium on RKEF expansion and accelerated investment in hydrometallurgy (HPAL). This strategic pivot toward Class I nickel production is imperative to valorize the massive limonite inventory and underpin the national EV battery ecosystem. Furthermore, this paper emphasizes that the HPAL transition must be tightly coupled with robust environmental, social, and governance (ESG) practices to mitigate ecological risks, particularly regarding tailings management and biodiversity protection in fragile small-island environments.